Peran Perempuan Dalam Pengembangan Kehidupan Berbasis Teknologi - Syafii, Syafii (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
Indonesia has reached a stepping stone in increasing equality and justice in education for both male and female citizens. That can be proven by the ratio of participation in education and literacy rates of men and women. Women's involvements in non-agricultural sector, participation of women in politics and the large number of women who are actively participating in progressing technology are true and concrete indicators. This article tries to observe how far the part and participation of women in the struggle to increase and develop technology. This is very meaningful because practically all of humanity is touched by technology, however crude it may be. If man were to live without technology in this age, it would be like a car with no wheels. Its means that technology has been a vital part of our lives, even if it may seem ghastly, scary, and can even trap and kill of the rights of women. But orderly technology has helped the participation of women in the public space; and with technology, many domestic jobs that have always been done by women can also be done by men.